The Importance of Ecological Accommodation Space and Sediment Supply for Cold-Water Coral Mound Formation, a Case Study From the Western Mediterranean Sea - Wang, Haozhuang; Titschack, Jürgen; Wienberg, Claudia; Korpanty, Chelsea; Hebbeln, Dierk (Frontiers in Marine Science, 2021)
The formation of cold-water coral (CWC) mounds is commonly seen as being the result of the sustained growth of framework-forming CWCs and the concurrent supply and deposition of terrigenous sediments under energetic hydrodynamic conditions. Yet only a limited number of studies investigated the complex interplay of the various hydrodynamic, sedimentological and biological processes involved in mound formation, which, however, focused on the environmental conditions promoting coral growth. Therefore, we are still lacking an in-depth understanding of the processes allowing the on-mound deposition of hemipelagic sediments, which contribute to two thirds of coral mound deposits. To investigate these processes over geological time and to evaluate their contribution to coral mound formation, we reconstructed changes in sediment transport and deposition by comparing sedimentological parameters (grain-size distribution, sediment composition, accumulation rates) of two sediment cores collected from a Mediterranean coral mound and the adjacent seafloor (off-mound). Our results showed that under a turbulent hydrodynamic regime promoting coral growth during the Early Holocene, the deposition of fine siliciclastic sediments shifted from the open seafloor to the coral mounds. This led to a high average mound aggradation rate of >130 cm kyr-1, while sedimentation rates in the adjacent off-mound area at the same time did not exceed 10 cm kyr-1. Thereby, the baffling of suspended sediments by the coral framework and their deposition within the ecological accommodation space provided by the corals seem to be key processes for mound formation. Although, it is commonly accepted that these processes play important roles in various sedimentary environments, our study provided for the first time, core-based empirical data proving the efficiency of these processes in coral mound environment. In addition, our approach to compare the grain-size distribution of the siliciclastic sediments deposited concurrently on a coral mound and on the adjacent seafloor allowed us to investigate the integrated influence of coral mound morphology and coral framework on the mound formation process. Based on these results, this study provides the first conceptual model for coral mound formation by applying sequence stratigraphic concepts, which highlights the interplay of the coral-framework baffling capacity, coral-derived ecological accommodation space and sediment supply.